2011
DOI: 10.1089/dna.2010.1161
|View full text |Cite
|
Sign up to set email alerts
|

SPAG4L, a Novel Nuclear Envelope Protein Involved in the Meiotic Stage of Spermatogenesis

Abstract: SUN domain-containing proteins belong to a novel protein family. To date, several members--SUN1, SUN2, SUN3, and SPAG4--have been identified as nuclear envelope (NE) proteins. In this study, we sought to characterize and define the potential function of SPAG4L, a newly identified SUN protein. Using bioinformatic analysis, we found that SPAG4L contained a conserved SUN domain in the C-terminal. Subcellular localization analysis indicated that the expression of green fluorescent protein-labeled full-length SPAG4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…The results presented above are clearly different from what was described in previous reports showing that Sun5 is mainly expressed during meiosis in the reticulum [12] and that Sun5 is located in the NE facing the acrosome and is not post-translationnally modified [11]. The main difference between our experiments and previous reports was the use of different antibodies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results presented above are clearly different from what was described in previous reports showing that Sun5 is mainly expressed during meiosis in the reticulum [12] and that Sun5 is located in the NE facing the acrosome and is not post-translationnally modified [11]. The main difference between our experiments and previous reports was the use of different antibodies.…”
Section: Discussioncontrasting
confidence: 99%
“…Contradictory results were published regarding Sun5 expression and localization. A first report has shown that Spag4l (alias of Sun5) and Spag4l-2 (a longer isoform of the same gene) are expressed after the meiosis and are located in the apical nuclear envelope of round spermatids facing the acrosome [11] whereas a second study reported an early and strong expression during meiosis [12]. Sun5 could therefore be one of the missing link between the nuclear envelope and the acroplaxome and may, with Dpy19l2, participate to the anchoring of the acroplaxome to the NE.…”
Section: Introductionmentioning
confidence: 99%
“…Male germ-line cells contain three other SUN proteins (Kracklauer et al, 2013), SUN3 (Göb et al, 2010), SUN4 (originally termed Spag4 (Shao et al, 1999;Tarnasky et al, 1998)) and SUN5 (also known as Spag4-like (Frohnert et al, 2011;Jiang et al, 2011)). Each of these conforms to the same general domain organization as SUN1/2 (Hasan et al, 2006;Liu et al, 2007).…”
Section: Mammalian Somatic Cells Contain Two Partially Redundant Sun mentioning
confidence: 99%
“…[5][6][7][8][9] LINC complexes and nuclear lamins form a solid scaffold for diverse functions including nuclear migration, 10 nuclear shaping and positioning,. 11,12 maintaining the centrosome-nucleus connection, 13,14 mechanotransduction, 15,16 DNA repair, 17,18 nuclear membrane spacing, cancer, and recessive cerebellar ataxia.…”
Section: Introductionmentioning
confidence: 99%